Blueprint for destigmatizing depression and increasing openness to treatment among adolescents using brief social contact-based videos: a qualitative study - DiGiovanni, Madeline; Jankowski, Samantha E.; Dixon, Lisa B.; Martin, Andrés; Amsalem, Doron (Frontiers in Child and Adolescent Psychiatry, 2024)
Depression is a major public health concern for adolescents, who exhibit low rates of connection to care despite significant needs. Although barriers to help-seeking such as stigma are well documented, interventions to address stigma and to increase help-seeking behavior are insufficient. Dissemination of short videos in social media offer a promising approach, but designing effective stimuli requires better insight into adolescents' perspectives of their own experiences, barriers, and possible interventions.We conducted 20 semi-structured interviews with adolescents recruited online via RecruitMe, a Columbia University clinical research registry, to explore their perceptions of depression stigma, barriers to care, the role of schools, and the role of brief video interventions. Thematic analysis guided our analytic approach.We developed a model consisting of three major domains:1) Barriers to Help-Seeking, which depicts participants debating their locus of control, naming social, parental, and peer stigma, and acknowledging systemic barriers; 2) Importance of School Systems, in which participants elaborated on the role of schools filling unmet needs and the importance of being taken care of; and 3) Role of Social Media Videos, characterized by adolescents who are seeking legitimacy, finding cultural authenticity, and working towards creating an accessible blueprint for better mental healthcare.We provide insights into adolescents' perceptions of help-seeking for depression and what nuances they would hope to see reflected in future interventions, most notably school-based interventions and peer social media videos. Our study offers a steppingstone towards the creation of brief, social contact-based video interventions focused on destigmatizing depression and promoting openness to treatment among adolescents.